1978
DOI: 10.1002/hlca.19780610514
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooct‐1‐en‐5‐yne. Preparation, spectroscopic characteristics and chemical reactivity

Abstract: Cyclooct-1-en-5-yne (3) has been obtained as an isolable, but highly reactive hydrocarbon by oxidation of cyclooct-5-ene-1,2-dihydrazone with lead tetraacetate (Scheme 2). Information regarding the structure and conformational mobility of 3 has been gained from the analysis of its 'Hand I3C-NMR. spectra and was found to agree with the results of force field calculations. Photolysis (206 nm) of 3 in solution has induced cleavage to butatriene and butadiene. The first band in the photoelectron spectrum of 3 (I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Wirz triene. Cyclooct-l-en-5-yne (5) has also been reported, 17 and it is less stable than 4. Moreover, Meier and his co-workers have recently observed that cycloocta-1,5dien-3-yne (6)18 is sufficiently stable for it to be isolated as a crystalline compound.…”
mentioning
confidence: 99%
“…Wirz triene. Cyclooct-l-en-5-yne (5) has also been reported, 17 and it is less stable than 4. Moreover, Meier and his co-workers have recently observed that cycloocta-1,5dien-3-yne (6)18 is sufficiently stable for it to be isolated as a crystalline compound.…”
mentioning
confidence: 99%